Global Innovation Index 2025 : innovation at a crossroads Global Innovation Index 2025 : innovation at a crossroads - 20001122d1996 m f0frey50 ba; World Intellectual Property Organization; World Intellectual Property Organization
The Global Innovation Index 2025 provides a detailed analysis of innovation performance across countries and regions, highlighting key trends and challenges at a pivotal moment for global innovation
Keywords: Research and development, Statistics -- Intellectual property